Immobilization of HPW on UiO-66-NH2 MOF as efficient catalyst for synthesis of furfuryl ether and alkyl levulinate as biofuel - Mulik, Nagesh; Bokade, Vijay (Molecular Catalysis, 2022)
Phosphotungustic Acid (HPW) is an inorganic super acid, that is highly soluble in polar solvents limiting its applicability as acid catalysis. To overcome these limitations immobilization of HPW was carried out at room temperature by protonation of-NH2 group of UiO-66-NH2 MOF to UiO-66-NH2-HPW. ATR-FTIR spectroscopy and XPS results confirmed the protonation and chemical interaction between HPW and UiO-66-NH2. STEM-EDS mapping showed homogeneous distribution of HPW on UiO-66-NH2. BET and NH3-TPD confirmed the reduction in specific surface area, total pore volume, and increase in total acidity for UiO-66-NH2-HPW. Further, powder XRD, SEM, and HR-TEM prevailed that there is no change in phase and morphology after post-synthetic modification of UiO-66-NH2. The prepared catalyst is found to be effective for etherification and alcoholysis of furfuryl alcohol (FALc) to Furfuryl ether (FE) and Alkyl levulinate (AL). UiO-66-NH2-HPW has shown 97 mol % FALc conversions in ethanolic media and 31 mol% Ethyl furfuryl ether (EFE) yield and 29 mol% Ethyl lev-ulinate (EL) yield. UiO-66-NH2-HPW is also found to be efficient for the multistep conversion of Furfural (FFR) to FALc, FE, and AL.
Keywords: Alcoholysis; etherification; Immobilization; Phosphotungstic acid; UiO-66-NH2-HPW